Pengaruh Pengalaman dan Kualitas Pelayanan terhadap Loyalitas yang dimediasi Kepuasan Pelanggan: Studi pada Konsumen Warmindo “X” di Kota Malang - Nasharuddin Mas; Dian Candra Dewi; Riris Zahrotul Fauziah (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study aims to examine the influence of customer experience and service quality on customer loyalty, with customer satisfaction as a mediating variable. Using a quantitative approach and explanatory research method, data was obtained through the distribution of questionnaires to 96 respondents who were selected through purposive sampling techniques and were consumers of Warmindo